FACTOR ANALYSIS ENFORCEMENT LAW AGAINST CRIMINAL ACTS OF ABUSE PERFORMED BY STUDENTS - Rezki Auliyah; Hijrah Adhyanti Mirzana2; Audyna Mayasari Muin (Awang Long Law Review, 2023)
The purpose of this study is to investigate the application of criminal law in response to acts of mistreatment done by students in Parepare City, as well as the factors that influence the application of criminal law in response to criminal acts of mistreatment committed by students in Parepare City. This study was carried out with the help of empirical research methodologies, including primary and secondary data, as well as data collection methods including interviews, observations, and analyses of published literature. After all of the preliminary and secondary data have been collected, they are then subjected to a qualitative analysis, after which they are characterized descriptively and organized systematically. According to the findings of the research, (1) the enforcement of criminal law in Parepare City against criminal actions of persecution conducted by students is not operating at an optimal level. Because of this, the administration of criminal law is conducted using a restorative justice approach at all stages of the process, including investigation, prosecution, and examination in court; (2) The legal and statutory considerations, law enforcement apparatus factors, and community factors are the three categories of elements that have an impact on how the criminal law is enforced in Parepare City in relation to the crime of persecution committed by students.